CHARACTERISTICS OF PHYSICAL PROPERTIES OF WOOD POWDER COMPOSITES AND BAGASSEAS CONSTRUCTION MATERIALS OF SHIP - Yulika Sari, Ersti; Nasution, Polaris; Ramdhan1, Fajri (Hasanuddin University, 2019)
Parameters for measuring the physical properties on this research are divided into three elements, including measurement of weight, water absorption, and density. This research was conducted from January to March 2018 to determine the physical properties of wood powder composites and bagasse. The manufacturing and testing process refers to the ASTM and JIS standards. Weight and density testing refer to the ASTM D 792 standard while the water absorption test refers to the JIS A5908 standard. The results showed that the density of wood powder was 0.4175 gr / cm3, and the bagasse was 0.3125 gr / cm3. Then, fiber absorption in units of volume to water and resin were 16.88% and 13.75% respectively. The results showed that the largest water absorption was found in composite wood powder 60% and bagasse 40%, which was 13.47%, and for the highest density values found in wood powder composites as much as 80% or 1,078.29 kg / m3